2019
DOI: 10.1088/1367-2630/ab0aa4
|View full text |Cite
|
Sign up to set email alerts
|

Regenerated amplification of terahertz spoof surface plasmon radiation

Abstract: Regenerated amplification induced by a Fabry-Perot (F-P) cavity is introduced to enhance the interaction efficiency of the free-electron-driven spoof surface plasmon. A direct-current electron beam flies above the meta-grating surface and seeds noise-level plasmonic waves. This weak signal experiences multiple back-and-forth regenerated amplifications in the F-P cavity loaded grating system, and the system outputs a pulsed radiation when the signal leaves the cavity. When compared with the condition without th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 35 publications
(40 reference statements)
0
9
0
Order By: Relevance
“…As an important SSP waveguide and interaction circuit, a metallic grating formed by single rectangular groove arrays has been proposed to develop free-electron-driven high-power radiation or amplifier sources [ 34 , 35 , 36 , 37 ]. It is shown that the SSP mode can be effectively excited and gradually amplified by an injected electron beam both on uniform and gradient meta-structures.…”
Section: Introductionmentioning
confidence: 99%
“…As an important SSP waveguide and interaction circuit, a metallic grating formed by single rectangular groove arrays has been proposed to develop free-electron-driven high-power radiation or amplifier sources [ 34 , 35 , 36 , 37 ]. It is shown that the SSP mode can be effectively excited and gradually amplified by an injected electron beam both on uniform and gradient meta-structures.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, extensive interest has also been attracted to its interaction with electron bunches for active applications. When a bunch of electrons parallelly fly over holy-structured metal surfaces (or various transformed structures), high-power coherent DSPP can be excited according to the Cherenkov condition [36][37][38], which is fundamentally different from that of Smith-Purcell radiation originating from zone folding [39][40][41][42]. The generated Cherenkov DSPP can only propagate along the metal surface, but has not been coupled out of the surface to form radiations.…”
Section: Introductionmentioning
confidence: 99%
“…However, within their limited choices, natural plasmonic materials often suffer from intrinsic high loss. , Besides, when the frequency comes to microwave and terahertz regimes, plasmonic effects of most materials become negligible, and the metals behave as perfect electric conductors. To develop the low-loss and flexible plasmons at low frequencies, the concepts of spoof surface plasmon polaritons (SSPPs) and effective surface plasmon polaritons (ESPPs), are respectively developed by periodically texturing the geometry of metals and tailoring the structural dispersion of electromagnetic (EM) modes in bounded waveguides. These methodologies have provided enormous possibilities in sensing, , focusing, , guiding, on-chip sources, generating vortex beams, , and novel applications based on controlling waves in subwavelength scale. Recently, we also proposed the spatial spectrum sampling by SSPPs, a method for retrieving the broadband evanescent information on targets and realizing subwavelength resolution imaging. Here, the SSPPs structure was employed as a sensitive spatial filter.…”
mentioning
confidence: 99%
“…23−25 To develop the low-loss and flexible plasmons at low frequencies, the concepts of spoof surface plasmon polaritons (SSPPs) 26 and effective surface plasmon polaritons (ESPPs), 27 are respectively developed by periodically texturing the geometry of metals and tailoring the structural dispersion of electromagnetic (EM) modes in bounded waveguides. These methodologies have provided enormous possibilities in sensing, 28,29 focusing, 30,31 guiding, 32−34 on-chip sources, 35 generating vortex beams, 36,37 and novel applications based on controlling waves in subwavelength scale. 38−41 Recently, we also proposed the spatial spectrum sampling by SSPPs, 42 a method for retrieving the broadband evanescent information on targets and realizing subwavelength resolution imaging.…”
mentioning
confidence: 99%